The Effect of Financial Distress and Corporate Social Responsibility on Tax Aggressiveness with Independent Commissioners as Moderating Variables - Setia Andrew Nugraha Marpaung; Rino Tam Cahyadi (CV Edujavare Publishing, 2026)
Tax revenue is a crucial source of state income; however, corporate tax compliance in Indonesia declined to 57.59% in 2024, indicating an increase in tax aggressiveness. This study examines the effects of financial distress and Corporate Social Responsibility (CSR) on tax aggressiveness, with independent commissioners as a moderating variable. Tax aggressiveness was measured using the Effective Tax Rate (ETR), financial distress using the Altman Z-Score, CSR using the Social Disclosure Index (SDI) based on GRI Standards 400, and independent commissioners by their proportion on the board of commissioners. Employing a quantitative causal approach, this study analyzed 103 manufacturing companies listed on the Indonesia Stock Exchange during 2021–2024, yielding 412 firm-year observations selected through purposive sampling. Panel data regression with the Common Effect Model (CEM) was applied. The findings reveal that financial distress and CSR disclosure positively and significantly affect tax aggressiveness. Moreover, independent commissioners do not moderate the relationship between financial distress, CSR, and tax aggressiveness, suggesting that their role remains largely administrative rather than functioning as an effective corporate governance mechanism in tax oversight.